2021
DOI: 10.3390/molecules26040935
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Pharmacological Potential of Coccoloba cowellii, an Endemic Endangered Plant from Cuba

Abstract: Coccoloba cowellii Britton (Polygonaceae) is an endemic and critically endangered plant that only grows in Camagüey, a province of Cuba. In this study, a total of 13 compounds were identified in a methanolic leaf extract, employing a dereplication of the UHPLC-HRMS data by means of feature-based molecular networking (FBMN) analysis in the Global Natural Products Social Molecular Network (GNPS), together with the interpretation of the MS/MS data and comparison with the literature. The major constituents were gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The total methanolic extract from C. cowellii leaves (hereafter referred to as total extract) was subjected to bioassay-guided fractionation following the scheme shown in Figure 1 . Given the promising results obtained for the total extract [ 8 ], the antifungal activity was employed as a guide for the fractionation and isolation of active compounds. Table 1 shows the results of the in vitro antifungal bioassays performed on the total extract and its fractions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The total methanolic extract from C. cowellii leaves (hereafter referred to as total extract) was subjected to bioassay-guided fractionation following the scheme shown in Figure 1 . Given the promising results obtained for the total extract [ 8 ], the antifungal activity was employed as a guide for the fractionation and isolation of active compounds. Table 1 shows the results of the in vitro antifungal bioassays performed on the total extract and its fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoid glycosides and glucuronides with quercetin and myricetin aglycon moiety have already been reported in relatively high concentrations in the total extract of C. cowellii leaves [ 8 ] and in other species of the genus [ 14 ]. In fact, compounds 1 – 3 from this study matched the ones previously identified in the total extract [ 8 ]. The other compounds identified in the methanol 90% fraction were reported in this species for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations